Comparison of fatigue characteristics for some selected structural materials under bending and torsion - Kurek, М.; Łagoda, Т. (Фізико-хімічна механіка матеріалів, 2011)
The paper presents a review of the multiaxial fatigue criteria including a ratio of normal and shear stresses. The paper also contains fatigue characteristics for bending and torsion of some selected constructional materials. The ratio of normal stresses to shear stresses was determined for the defined number of cycles Nf in the range 5⋅10⁴÷2⋅10⁶. Moreover, from the performed analysis of fatigue equations and the relative difference R it appears that materials can be divided into groups for which it is possible or it is not possible to apply the constant value of the considered ratio in the criteria including this ratio. Подано огляд критеріїв багатовісної втоми, які охоплюють співвідношення нормальних та зсувних напружень. Розглянуто втомні характеристики деяких вибраних конструкційних матеріалів за згину та закруту. Визначено співвідношення нормальних до зсувних напружень для певної кількості циклів Nf у діапазоні 5⋅10⁴÷2⋅10⁶. Із результатів аналізу втомних характеристик та відносної зміни R виявлено, що матеріали можна поділити на дві групи, для яких доцільно чи недоцільно застосувати стале значення розглянутого в критерії співвідношення. Дан обзор критериев многоосной усталости, которые включают соотношения нормальных и напряжений сдвига. Рассмотрены усталостные характеристики некоторых избранных конструкционных материалов при изгибе и кручении. Определено соотношение нормальных и напряжений сдвига для определенного числа циклов Nf в диапазоне 5⋅10⁴÷2⋅10⁶. Из результатов анализа усталостных характеристик и относительной разницы R установлено, что материалы можно разделить на две группы, для которых возможно или невозможно применить постоянное значение рассмотренного в критерии соотношения.